Alternative education paths for pregnant girls and young mothers in Tanzania. Issue 1 (3rd February 2021) - Fute, Antony Zakaria; Wan, Xiulan
Abstract: This paper aimed to elaborate the importance of investing in girls' educating for socio‐economic development, by describing the Tanzania's Alternative Education Paths, following the ban of pregnant girls and young mothers in public regular schools. Qualitative design (document review) was used to collect and analyze data from different documents and official websites such as World Bank, UNESCO, UNICEF, and Ministries of Education. 3.6 million Primary and secondary aged children are out of school, and 5, 500 girls drop out of school every year because of pregnancy in Tanzania. Open schools and Folk Development Colleges are not in good quality but opted as alternative paths for dropouts. Chinese adult education system and provision of sex education are few suggestions lamented in this article. Girls' education is essential and with the additional possible alternatives of ensuring pregnant girls' right to education, the paper will help policymakers to think about the best option of ensuring pregnant girls' and young mothers' right to education.